Revenge of the flower girls - Ziegler, Jennifer, 1967- (Scholastic Press, 2014)
When their usual summer plans are upended by their big sister's wedding, triplets Dawn, Darby, and Delaney struggle with their dislike for the groom-to-be, a sentiment that compels them to reunite their sister with her fun-loving ex.